Database for "Evidence of stereotyped contact call use in narwhal (Monodon monoceros) mother-calf communication" - Audra E. Ames (11181799); Susanna B. Blackwell (823837); Outi M. Tervo (292082); Mads Peter Heide-Jørgensen (6418829) (2021)
This database consists of three files, Freya_FS.txt, Thora_FS.txt, and Eistla_FS.txt. Each file lasts for the duration of each whale's deployment, and is on a one-second time-line. The files have the following format: 8/24/16 13:09:070.0contactCallNaNNaN 8/24/16 13:09:080.0NaNNaNNaN 8/24/16 13:09:090.0NaNNaNNaN The first column includes the date (mm/dd/yy) and time (hh:mm:ss); the second column gives the whale's depth (in meters); the third, fourth, and fifth columns indicate the presence of calls in the record at that time (see below). In Freya's record, there was never more than one call in a second, so her record has only one call column. Below is a list of definitions for the call columns: - contactCall : contact call by tagged whale - tonalCall : tonal call by tagged whale - pulsedCall : pulsed call by tagged whale - mixedCall : mixed call by tagged whale - otherWhale : unspecified call made by whale other than the one carrying the tag - unknownWhale : unspecified call made either by tagged whale or other whale In addition, Eistla's record has additional categories for calls ascribed to her calf: - calfContactCall - calfTonalCall - calfPulsedCall - calfMixedCall So for example, if at time X the third, fourth, and fifth columns include "contactCall otherWhale otherWhale" then three calls were started at time X, a contact call by the whale carrying the tag, and two unspecified calls by nearby whales.